Beef seasoning sauce filling equipment - HAN YUBAO; HE DEJIN; MA ZHIGANG (2023)
The utility model discloses beef sauce filling equipment, which belongs to the technical field of filling equipment and comprises a conveying belt, a mounting opening is formed in the conveying belt, and a tank body is suitable for being placed in the mounting opening; the interior of the bearing tank is suitable for containing seasoning sauce, a feeding port is formed in the bearing tank, a discharging port is formed in the bottom of the bearing tank, a stirring rod is installed in the bearing tank, and a plurality of sets of stirring blades are installed in the stirring rod; the variable body is installed below the bearing tank, and a first connecting opening is formed in the top of the variable body and connected with the discharging opening; a plurality of sets of discharging bodies arranged in the direction of the conveying line are installed at the bottom of the variable body, the discharging bodies communicate with the variable body, and switch valves are installed on the multiple sets of discharging b